Local depletion of two larger Duikers in the Oban Hills Region, Nigeria (2012)
Across West and Central Africa, duikers are important for trade and consumption; their populations are expected to become depleted. Reliable data on their status are scanty in Nigeria. We assessed duiker populations in the Oban Sector of Cross River National Park through diurnal and nocturnal surveys along 32 transects of 2 km each. After 508-km survey effort, only Ogilby’s duiker (Cephalophus ogilbyi) and blue duiker (Philantomba monticola) were recorded. Using habitat as a covariate in modeling detection probability in DISTANCE 6.0, we estimated densities for the blue duiker ranging from 15.5 (95% CI: 7.8–30.9) in the core, 5.8 (CI: 2.6–12.9) in the buffer and 0.9 (CI: 0.09–10.1) km² in farm fallow to no duikers in the plantation. For Ogilby’s duiker, densities ranged from 1.6 (95% CI: 0.7–3.7) km² in the core, 2.0 (CI: 0.8–5.1) in buffer to no duikers in farm fallow and plantation. The apparent absence of yellow-backed and Bay duikers may indicate local depletion. We call on all stakeholders to rise up to the challenge of rescuing this biological hotspot in Nigeria from further degradation and species loss through improved funding for well-equipped field staff and institutionalized community wildlife management